THE ROLE OF INDONESIAN PHARMACIST ASSOCIATION ON THE IMPLEMENTATION OF PHARMATEUTICAL SERVICES STANDARD IN PHARMACY IN DIY - Ankie Aulia Rachmandani; Sampurno Sampurno; Achmad Purnomo (Faculty of Pharmacy, Universitas Gadjah Mada)
The public guidance of pharmaceutical services policy standard has been provided by the government throughIndonesian Health Ministrial Decree No. 1027/Menkes/SK/IX/2004. This policy, however, i still unimplementedyet, and seems need to be further evaluated. Study on the role of Indonesian Pharmacist Association (IAI) on theImplementation of pharmaceutical services standard in the pharmacy of DIY region was conducted. The study aimsto explore the IAI effort in implementing the government policy in DIY region, including services, learning andprotection. An explorative descriptive research was carried out. The data were collected through observation using passiveparticipatory model, indepth interview to the management of IAI and chemist management in DIY region. A total of17 respondents, covering chairman and secretary of DIY IAI, pharmacist and chemist management were interviewed.Triangulation was also conducted to pharmacist which manage the chemists.The study results show for service role, the policy level IAI seeks to play its role by issuing movement “NoPharmacist No Service”, but the operational level this movement has not been as expected. The protection role, IAIseeks advocacy function by providing protection to its members. In contrast the networking function has not beenable to lift the pharmacist image in society. For learning role, continuing professional education activities must be continuously conducted with some notification for improvement. The awareness of pharmacist in improving theircompetency should be increased through improvement of accountability of IAI. Key words: Indonesian Health Ministrial Decree No. 1027, IAI, pharmaceutical services policy